First Time Experience of Being a Father in Adapting to Postpartum Period in Indonesia Setting - Ambarwati, Winarsih Nur; Ihtiarini, Risalatul (Jurnal Berita Ilmu Keperawatan, 2019)
The post partum period is an extraordinary transition for a father in his first experience. Research results have shown that fathers have a very large role in the health and welfare of mothers and children. However, often the father has difficulty in adapting and carrying out his role due to lack of knowledge, skills and support. The lack of research exploring the experience, needs and behavior of fathers in adapting to postpartum causes a lack of references. The objective of is to explore fathers’ experience in adapting to postpartum period in Indonesia. The research design is qualitative research by descriptive phenomenology study.Technique sampling is by purposive sampling. The number of participants is 10 fathers who get their first child . Data were collected through in-depth interviews. Data were analysed by qualitative analysis with Colaizzi method. The result is the first psychological experience of being a father in adapting to postpartum includes positive and negative feelings. Positive feelings include happiness and gratitude. Negative feelings include confusion, difficulty adapting to new roles, feeling worried, changing patterns of relationships with wives, feelings of neglect, expected and required to be able to understand wives and provide support, lack of information from health workers relating to postpartum care. Conclusion: Father's first experience of adapting to postpartum is more perceived negative feelings. Recommendation : Health professionals are required to be able to understand the psychological condition of the father and then be able to provide the necessary support so that the father can adapt well and have a positive influence on the mother and baby.